The Effect of Sales Promotion towards Impulse Buying with Lifestyle as an Intervening Variable during the Covid-19 Pandemic - Sarah Marwa Maitsa; Sherly Artadita (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2022)
The development of the digital technology era greatly affects daily life to be easier. E-Commerce is one of the technologies that are in great demand in this digital technology era. In addition, the Covid-19 pandemic has caused people to use online media electronic every day. This phenomenon can lead to the emergence of impulsive consumer behavior, especially when E-Commerce offers promotions that can give benefits to consumers. This study aims to determine how much sales promotion influence has on the impulse buying behavior of Generation Z Shopee users through lifestyle as an intervening variable. The method used in this research was the quantitative method with descriptive analysis and Structural Equation Modelling (SEM-PLS) analysis technique using SmartPLS 3.2.9 software. The sample used was determined through probability sampling with a simple random sampling approach with a total of 385 respondents. This study concludes that the results of hypothesis testing indicated sales promotion has a positive and significant effect on lifestyle, lifestyle has a positive and significant effect on impulse buying, sales promotion has a positive and significant effect on impulse buying and sales promotion has a positive and significant effect on impulse buying through lifestyle, which means lifestyle partially mediates.